Pro‐gastrin‐releasing peptide and outcome in patients with heart failure and anaemia: results from the RED‐HF study. (25th August 2018) - Ueland, Thor; Gullestad, Lars; Kou, Lei; Aukrust, Pål; Anand, Inderjit S.; Broughton, Marianne Nordlund; McMurray, John J.; van Veldhuisen, Dirk J.; Warren, David J.; Bolstad, Nils
Abstract: Aims: Neuroendocrine activation is associated with poor outcome in heart failure (HF). The neuropeptide gastrin‐releasing peptide (GRP), derived from the precursor proGRP1‐125 (proGRP), has recently been implicated in inflammation and wound repair. We investigated the predictive value of proGRP on clinical outcomes in HF patients with reduced ejection fraction. Methods and results: The association between plasma proGRP (time‐resolved immunofluorometric assay) and the primary endpoint of death from any cause or first hospitalization for worsening of HF was evaluated using multivariable Cox proportional hazard models in 1541 patients with systolic HF and mild to moderate anaemia, enrolled in the Reduction of Events by Darbepoetin alfa in Heart Failure (RED‐HF) trial. Median proGRP levels in the RED‐HF cohort were markedly increased [95 ng/L (25th, 75th percentile, 69–129 ng/L)] with 64% patients above the 80 ng/L reference limit. Baseline proGRP correlated with estimated glomerular filtration rate ( r  = 0.52), N terminal pro brain natriuretic peptide ( r  = 0.33), troponin T ( r  = 0.34), and haemoglobin ( r  = 0.16) (all P  < 0.001). The incidence outcome increased with increasing tertiles of baseline proGRP (primary endpoint third tertile vs. the lowest tertile; hazard ratio 1.91; 95% confidence interval 1.60–2.28, P  < 0.001). However, these associations were markedly attenuated and non‐significant in adjusted models. No interaction between baseline proGRP and the effect of darbepoetin alfa treatment was detected. Moreover, no significant association between changes in proGRP during 6 month follow‐up and outcome was observed. Conclusions: Pro‐gastrin‐releasing peptide is increased in patients with HF with reduced ejection fraction and anaemia, in particular in patients with poor renal function. However, proGRP adds little as a prognostic marker on top of conventional HF risk factors.